Hot issue markets and industry effect on IPO underpricing in Norway - Folkvord, Birgitte (2018)
In this dissertation, I use a dataset of Norwegian IPOs from 1993 to 2018 to investigate IPO underpricing. I find an average underpricing of 5.47%, this finding is statistically significant at the 1% level. This proves that there is underpricing present in the sample, and the underpricing percentage is a middle value compared to other studies on the Norwegian IPO market. I find evidence of industry and hot issue markets effect in my dataset. Industries help explain 1.01% of the underpricing in the Norwegian market, and 2.98% of the underpricing during hot issue markets. My findings suggest that issuers time their IPOs to coincide with favorable issue periods, this is consistent with the findings of Ibbotson and Jaffe (1975). This is in line with information asymmetry and behavioral explanations for IPO underpricing. However, these effects only explain a small part of the variance in IPO underpricing, therefore there is room for further research on this topic. Especially when it comes to the differences in explanatory variables in hot versus cold issue markets.